2016
DOI: 10.1371/journal.pone.0151980
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Sample Processing Method for Rapid Detection of Tuberculosis in the Stool of Pediatric Patients Using the Xpert MTB/RIF Assay

Abstract: BackgroundTuberculosis (TB) is difficult to diagnose in children using molecular tests, because children have difficulty providing respiratory samples. Stool could replace sputum for diagnostic TB testing if adequate sample processing techniques were available.MethodsWe developed a rapid method to process large volumes of stool for downstream testing by the Xpert MTB/RIF (Xpert) TB-detection assay. The method was tested and optimized on stool samples spiked with known numbers of M. tuberculosis colony forming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 32 publications
(46 reference statements)
6
65
1
Order By: Relevance
“…In our current study, stool Xpert was positive only in children with radiologically severe TB, with a sensitivity of 82% for smear-positive TB and 45% for bacteriologically confirmed cases with severe disease. This is consistent with a laboratory study where the level of detection for Xpert on Macaque stools was determined to be approximately 1000 colony forming units (CFU)/mL (36), whereas in respiratory samples it is approximately 100 CFU/mL(37). …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our current study, stool Xpert was positive only in children with radiologically severe TB, with a sensitivity of 82% for smear-positive TB and 45% for bacteriologically confirmed cases with severe disease. This is consistent with a laboratory study where the level of detection for Xpert on Macaque stools was determined to be approximately 1000 colony forming units (CFU)/mL (36), whereas in respiratory samples it is approximately 100 CFU/mL(37). …”
Section: Discussionsupporting
confidence: 89%
“…The different protocols used in published studies could partly explain the variable results observed. For molecular analysis, stool samples require careful processing to remove PCR inhibitors and particulate matter that can interfere with assay performance (36, 39-41). Stool processing currently remains relatively labor intensive, but work is ongoing to develop centrifugation-free protocols applicable to primary/ district level healthcare facilities (36).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that using larger sample volumes, of 0.6 g25 and 2 cm 3 ,26 and pre-treatment with a stool-processing buffer to inactivate PCR inhibitors,25 achieves greater diagnostic yield of the stool Xpert test.…”
Section: Discussionmentioning
confidence: 99%
“…75,76 Detecting the organism in stool may be an option where GeneXpert MTB/RIF testing is available. 77,78 …”
Section: Diagnosismentioning
confidence: 99%